The Oscillating Potential Model of Visually Induced Vection. (November 2017) - Seno, Takeharu; Sawai, Ken-ichi; Kanaya, Hidetoshi; Wakebe, Toshihiro; Ogawa, Masaki; Fujii, Yoshitaka; Palmisano, Stephen
Visually induced illusions of self-motion are often referred to as vection . This article developed and tested a model of responding to visually induced vection. We first constructed a mathematical model based on well-documented characteristics of vection and human behavioral responses to this illusion. We then conducted 10, 000 virtual trial simulations using this Oscillating Potential Vection Model (OPVM) . OPVM was used to generate simulated vection onset, duration, and magnitude responses for each of these trials. Finally, we compared the properties of OPVM's simulated vection responses with real responses obtained in seven different laboratory-based vection experiments. The OPVM output was found to compare favorably with the empirically obtained vection data.